Intra‐His bundle block with Wenckebach phenomenon. Issue 5 (10th August 2021) - Kumar, Sharath; Thomas, Garry; Newman, David; Crystal, Eugene; Lashevsky, Ilan
Abstract: A 66‐year‐old lady presented with shortness of breath and a Wenckebach atrioventricular (AV) conduction pattern on the ECG. The electrophysiologic study showed split‐His potentials and intra‐Hisian Wenckebach. The case highlights the interesting finding of Wenckebach conduction in the His bundle. Abstract : A 66‐year‐old lady presented with shortness of breath and a Wenckebach conduction pattern on the ECG. The EP study showed split his potentials and intrahisian Wenckebach. The case highlights the interesting finding of Wenckebach in the His bundle.